EFEK RADIASI SINAR GAMMA (CO-60) UNTUK PERBAIKAN MUTU BENIH DAN BIBIT TSS ( True Shallot Seed) TANAMAN BAWANG MERAH (Allium ascalonicum L.) VARIETAS BAUJI - Nurhiza Purnama Wulandari; Juli Santoso; Ida Retno Moeljani (UPN VETERAN JAWA TIMUR, 2018)
This research aims to improve seed quality and TSS seedlings and to get TSS optimum radiation dose to improve seed quality and TSS shallots seedlings Bauji variety. TSS seeds irradiated in BATAN (National Nuclear Energy Agency) with five doses of radiation (5, 15, 25, 35, and 45 Gy). Seed planted in Randuagung village, Singosari-Malang. Research held based on Completely Randomized Design (RAL) by single factor, 6 treatments repeated 3 times. The results of this research are gamma ray radiation co-60 is significant to germination percentage, rate of germination, value of germination and index vigor. For variable amount of life seeds known from the amount of TSS seeds germinated are more than the amount of life seedlings. While in production, gamma ray radiation co-60 are significants to wet weight and dry weight but it no significant to amount of tubers. The conclusion are gamma ray radiation co-60 was able to improve the quality of seed but haven’t been able to improve the quality of TSS seedlings. Radiation dose 5 Gy is the best dose to improve the quality of TSS shallot seeds Bauji variety.